Fusion of Aza‐ and Oxadiborepins with Furans in a Reversible Ring‐Opening Process Furnishes Versatile Building Blocks for Extended π‐Conjugated Materials. Issue 63 (2nd September 2022) - Bachmann, Jonas; Helbig, Andreas; Crumbach, Merian; Krummenacher, Ivo; Braunschweig, Holger; Helten, Holger
Abstract: A modular synthesis of both difurooxa‐ and difuroazadiborepins from a common precursor is demonstrated. Starting from 2, 2′‐bifuran, after protection of the positions 5 and 5' with bulky silyl groups, formation of the novel polycycles proceeds through opening of the furan rings to a dialkyne and subsequent re‐cyclization in the borylation step. The resulting bifuran‐fused diborepins show pronounced stability, highly planar tricyclic structures, and intense blue light emission. Deprotection and transformation into dibrominated building blocks that can be incorporated into π‐extended materials can be performed in one step. Detailed DFT calculations provide information about the aromaticity of the constituent rings of this polycycle. Abstract : Merging furan rings with 1, 2, 7‐oxa‐ and ‐azadiborepins. This modular synthesis proceeds through a reversible ring‐opening process and furnishes the novel heteropolyaromatic compounds from a common precursor. The tricyclic systems are overall aromatic, and weak aromaticity in the diboron heterocycles favors π electron delocalization over the bifuran unit. The π‐conjugated system is easily extended through the α‐positions of the furan rings.